From inner-bay preservation to offshore dissipation: Spatiotemporal patterns and tracing of pharmaceuticals in Shenzhen Bay of the greater bay area, South China - Guangyang Cheng; Haoshuai Li; Lei Xing; Yang Zhou; Danxu Guo; Zimin Wang; Siqi Zhao; Zongshan Zhao; Shuhong Fang; Fang Chen; Rui Bao (Marine Pollution Bulletin, 2026)

Maternal exposure to particulate matter during pregnancy and offspring liver function - Ziyi Zhou; Bin Sun; Yudiyang Ma; Ning Chen; Haibo Li; Wenpu Shao; Rui Tang; Lei Zheng; Meiqi Xing; Xinru Zhao; Yibing Zhu; Yaohua Tian (Environmental Pollution, 2026)

Janus dual-nitride heterostructure on nanoporous metal for highly selective urea oxidation-assisted hydrogen production - Zhi-Lan Zhou; Jin-Peng Li; Ying Wang; Rui-Qi Yao; Xin-Ying Sun; Shu-Pei Zeng; Yun-Fei Chang; Gao-Feng Han; Tong-Hui Wang; Zi Wen; Hang Shi; Xing-You Lang; et al. (Chemical Engineering Journal, 2026)

Extracellular polymeric substances Govern granule size differentiation and microbial assembly in denitratation–Anammox systems - Jinyan Wang; Shenbin Cao; Xing Li; Zhiwei Zhou; Rui Du (Bioresource Technology, 2026)

Energy optimization and life cycle assessment of an industrial-scale ammonia stripping process for aging landfill leachate pretreatment - Yanyu Yang; Rui Zhang; Xu Xing; Youcai Zhao; Meilan Zhang; Tao Zhou (Process Safety and Environmental Protection, 2026)

Sex-specific associations between prenatal PM2.5 exposure and reproductive hormone levels in offspring aged 1–2 years: A prospective birth cohort study - Wenpu Shao; Shengli Jiang; Yudiyang Ma; Ning Chen; Zhiping Niu; Rui Tang; Meiqi Xing; Lei Zheng; Xinru Zhao; Bin Sun; Haibo Li; Ziyi Zhou; et al. (Environmental Research, 2026)

Paleoclimate and sediment provenance evolution revealed by terrestrial geochemical records from the carboniferous–cretaceous liupanshan basin, northwestern China - Qi-Fang Zheng; Rui Zhao; Shi-Qiang Xia; Yu-Zhou Zheng; Dao-Qing Zhou; Xing-Zhong Hao (Applied Geophysics, 2026)

PTPσ mediates the integration of grafted neuronal tissueoids with host neural pathways after complete spinal cord injury - Rui Mao; Yuan-Huan Ma; Jin-Yuan Xiao; Qing-Shuai Wei; Yin-Chun Zhao; Qi-Xing Hu; Hou-Ge Li; Ke-Jun Zhang; Lai-Jian Wang; Hui-Juan Shi; Li-Zhi Peng; Jun-Hua Wang; et al. (Science China Life Sciences, 2026)

A detoxifying multi-strain probiotic formula attenuates toxicity induced by heavy metals and phthalates - Rui Xiao; Yaqi Yu; Deshan Ning; Zehua Chen; Chuguang Ning; Leilei Yu; Shumao Cui; Jianxin Zhao; Gang Wang; Yong Zhou; Xing Jin (Food Research International, 2026)

Position dependent elasticity of the anterior talofibular ligament in healthy young women: an in-vivo shear wave elastography study - Zili Chen; Wan Zhou; Hao Liang; Xing Liu; Yibo Li; Li Yang; Huijuan Xiang; Rui Du (European Journal of Applied Physiology, 2026)

A phase field fracture model for rock creep: Theoretical framework and engineering applications - Rui Liu; Shuwei Zhou; Shikang Qin; Chengkai Zhang; Meng Xing (Computers and Geotechnics, 2026)

Cell-specific gene expression plasticity in response to hypoxia promotes high-altitude adaptive evolution - Wen-Tian Wei; Ze Yan; Hui Wu; Ming-Liang Zhou; Dong-Xin Mo; Xing Wan; Rui Ma; Mei-Ming Wu; Jia-Hui Huang; Ya-Jing Liu; Ji Yang; Meng-Hua Li (Science China Life Sciences, 2026)

Monodisperse lutetium-177-labeled poly(lactic acid) microspheres for radioembolization therapy of hepatocellular carcinoma - Qing-Rong Jiang; Ping He; Ling-Yun Guo; Qi-Yi Mo; Xing-Long Zhou; Wei Wang; Zhuang Liu; Rui Xie; Da-Wei Pan; Wen-Jie Zhang; Xiao-Jie Ju; Liang-Yin Chu (Chemical Engineering Journal, 2026)

Roles of vertical light-conducting carriers applied in microalgal-bacterial biofilm for enhanced nitrogen and phosphorus removal - Yong-Sen Cao; Yong-Qi Cheng; Yi Liu; Xing-Rui Zhou; Cong-Cong Tang; Zhang-Wei He; Wen-Qiong Wang; Yu Tian; Xiaochang C. Wang (Bioresource Technology, 2026)

The protective effects of alkaloids from Stephania tetrandra S. Moore on H9C2 cardiomyocytes - Yan-nan Ji; Ran Zhou; Zhi-hui Zhang; Xing-ru Gao; Si-qian Yang; Pu-yu Yang; Zi-shan Chen; Jun-li Sha; Jing-yu He; Yue-feng Zhang; Tie-jun Zhang; Yu-cheng Gu; et al. (Natural Product Research, 2026)

Corrigendum to “Hepatocyte mitochondrial DNA activated store-operated Ca2+ entry via Stim1/Orai1-induced podocyte injury in trichloroethylene sensitized mice: A new insight in liver and kidney crosstalk” [Toxicology and Applied Pharmacology Volume 503, October 2025, 117465]. - Luo-lun Dong; Xue-qian Jia; Hai-bo Xie; Li-fu Zhu; Peng-cheng Zhou; Rui-xuan Cheng; Chun-lin Cao; Qi-xing Zhu; Jia-xiang Zhang (Toxicology and Applied Pharmacology, 2025)

Sequential preservation of fresh-cut Agaricus bisporus: Sodium hyaluronate/p-coumaric acid edible coating followed by carvacrol vapor treatment for enhanced shelf-life and quality maintenance - Mengsha Ma; Rui Song; Yanjing Zhou; Ziwen Li; Xing Wang; Yunjie Zhang; Xingyu Yang; Jie Zhou; Fansheng Cheng; Xia Liu; Demei Meng (Food Packaging and Shelf Life, 2025)

Dual-mechanism defect engineering of multi-enzyme embedded ZIF-8 for efficient anthocyanin extraction from black rice - Mengyuan Cao; Bicong Wang; Yuchao Deng; Da-Wei Pan; Xiao-Jie Ju; Rui Xie; Zhuang Liu; Xing-Long Zhou; Mao-Jie Zhang; Wei Wang; Liang-Yin Chu (Chemical Engineering Journal, 2025)

Sediment amplifies organic matter cycling and nutrients feedback in eutrophic lake zones - Junfeng Xing; Yuping Zhou; Ding He; Fen Guo; Penghui Li; Yuan Zhang; Rui Lv; Runze Xue; Changqing Liu; Yihua Xiao (Water Research, 2025)

Hepatocyte mitochondrial DNA activated store-operated Ca2+ entry via Stim1/Orai1-induced podocyte injury in trichloroethylene sensitized mice: A new insight in liver and kidney crosstalk - Luo-lun Dong; Xue-qian Jia; Hai-bo Xie; Li-fu Zhu; Peng-cheng Zhou; Rui-xuan Cheng; Chun-lin Cao; Qi-xing Zhu; Jia-xiang Zhang (Toxicology and Applied Pharmacology, 2025)

A Co(III)-dipyrazolate framework for atmospheric CO2 photoreduction - Yingjie Wang; Xiang-Jing Kong; Guang-Rui Si; Tao He; Da-Yu Chen; Jian-Yu Zhang; Na Xing; A-Wu Zhou; Jian-Rong Li (Chemical Engineering Journal, 2025)

Enhancing the anti-inflammatory efficacy of polysaccharides through processing techniques: a case study on Atractylodes macrocephala - Hong-Da Xuan; Sheng-Nan Shen; Chun-Jin Fu; Jie Zhou; Rui-Xing Chen; Jun-Zhe Zhang; Xiao-Xia Liu; Feng-Qin Li; Yi-Fan Zhao; Dong Zhang; Hai-Ning Lyu; Fang Wang (Natural Product Research, 2025)

Insight into unloading and geostress characteristics of high slopes based on valley evolution: a case study in Luding county, China - Hongfu Zhou; Shuwu Li; Fan Yang; Tian Fang; Rui Li; Jingyi Xue; Jinpeng Hu; Jiang Xing (Bulletin of Engineering Geology and the Environment, 2025)

Synthetic microbiome and biochar enhanced human feces aerobic mesophilic composting - Xiaoyu Cai; Jing Wang; Kun Feng; Huihui Zhou; Chuan Chen; Chuandong Wu; Rui Fang; Defeng Xing (Resources, Conservation and Recycling, 2025)

Epigenetics in the modern era of crop improvements - Yan Xue; Xiaofeng Cao; Xiangsong Chen; Xian Deng; Xing Wang Deng; Yong Ding; Aiwu Dong; Cheng-Guo Duan; Xiaofeng Fang; Lei Gong; Zhizhong Gong; Xiaofeng Gu; et al. (Science China Life Sciences, 2025)
Epigenetic mechanisms are integral to plant growth, development, and adaptation to environmental stimuli. Over the past two decades, our comprehension of these complex regulatory processes has expanded remarkably, producing a substantial body of knowledge on both locus-specific mechanisms and genome-wide regulatory patterns. Studies initially grounded in the model plant Arabidopsis have been broadened to encompass a diverse array of crop species, revealing the multifaceted roles of epigenetics in physiological and agronomic traits. With recent technological advancements, epigenetic regulations at the single-cell level and at the large-scale population level are emerging as new focuses. This review offers an in-depth synthesis of the diverse epigenetic regulations, detailing the catalytic machinery and regulatory functions. It delves into the intricate interplay among various epigenetic elements and their collective influence on the modulation of crop traits. Furthermore, it examines recent breakthroughs in technologies for epigenetic modifications and their integration into strategies for crop improvement. The review underscores the transformative potential of epigenetic strategies in bolstering crop performance, advocating for the development of efficient tools to fully exploit the agricultural benefits of epigenetic insights.

Deep Learning-Based Surrogate-Assisted Intelligent Optimization Framework for Reservoir Production Schemes - Lian Wang; Hehua Wang; Liehui Zhang; Liang Zhang; Rui Deng; Bing Xu; Xing Zhao; Chunxiang Zhou; Li Fan; Xindong Lv; Junda Wu (Natural Resources Research, 2025)

Microrna363-5p targets thrombospondin3 to regulate pathological cardiac remodeling - Yu-kun Ma; Xin-yi Han; Shu-huai Zan; Hui-ting Liu; Xue-yan Zhou; Dan-xue Zhao; Rui Xing; Peng Zhao (Molecular and Cellular Biochemistry, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Grevillosides R-S: glucosides of 5-alkylresorcinol derivatives from roots of Ardisia crispa (Thunb.) A. DC - Xing-xiang Long; Shuang Zhang; Li-juan Xiang; Rui-hang Hu; Ting-ting Feng; Ying Zhou; Xin Yin (Natural Product Research, 2025)

Corrigendum to “Vimentin rearrangement by phosphorylation is beneficial for porcine reproductive and respiratory syndrome virus replication in vitro” [Vet. Microbiol. 259 (2021) 109133] - Xin-xian Zheng; Rui Li; Songlin Qiao; Xin-xin Chen; Longxiang Zhang; Qingxia Lu; Guangxu Xing; En-min Zhou; Gaiping Zhang (Veterinary Microbiology, 2025)

A review of nanoscale MnOx-based materials: Catalytic and oxidative properties for pollutant degradation in multiple mediums - Zi-Chun Lu; Hai-Zhu Liu; Rui Zhang; Bin Li; Jin-Xing Zhou; Hai-Feng Su (Journal of Water Process Engineering, 2024)

Peering through the hedge: Multiple datasets yield insights into the phylogenetic relationships and incongruences in the tribe Lilieae (Liliaceae) - Deng-Feng Xie; Juan Li; Jia-Hui Sun; Rui-Yu Cheng; Yuan Wang; Bo-Ni Song; Xing-Jin He; Song-Dong Zhou (Molecular Phylogenetics and Evolution, 2024)

Dexmedetomidine attenuates ferroptosis by Keap1-Nrf2/HO-1 pathway in LPS-induced acute kidney injury - Rui-Rui Luo; Jing Yang; Yan-Lin Sun; Bi-Ying Zhou; Si-Xuan Zhou; Guo-Xing Zhang; Ai-Xiang Yang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Effects of active vitamin D analogs and calcimimetic agents on PTH and bone mineral biomarkers in hemodialysis patients with SHPT: a network meta-analysis - Xing Liu; Yichen Liu; Peimin Zheng; Xun Xie; Zhouzhou Li; Rui Yang; Lie Jin; Ziwei Mei; Peipei Chen; Limei Zhou (European Journal of Clinical Pharmacology, 2024)

Effects of carbonation modification on shear performance of recycled aggregate concrete beams: Test and mechanism analysis - Yingwu Zhou; Wenzhuo Xu; Jiahao Zhuang; Wenwei Lin; Feng Xing; Rui Hu (Engineering Structures, 2024)

Isolation and Characterization of a Novel Vibrio Phage vB_ValA_R15Z - Huifang Li; Wanxuan Zhong; Xinyu Zhang; Zhang Rui; Yunlan Yang; Juntian Xu; Jie Gao; Xing Zhou; Jie Wu; Jie Xu (Current Microbiology, 2024)

Slide-controlling modes and classification system of the mélange high slopes: insight into a disaster-causing mechanism of the Jinsha River mélange belt in the eastern Tibetan Plateau - Hongfu Zhou; Meng Wang; Jingyi Xue; Rui Li; Jinpeng Hu; Jiang Xing; Tian Fang (Bulletin of Engineering Geology and the Environment, 2024)

Probing rotaxane dynamics with 19F NMR/MRI: Unveiling the roles of mechanical bond and steric hindrance - Yu Li; Man Luo; Mou Jiang; Rui Zhou; Wanrong Yang; Shenhui Li; Fang Wang; Lijun Zhu; Pei He; Minghui Yang; Xin Zhou; Zhong-Xing Jiang; et al. (Analytica Chimica Acta, 2024)

Quercetin regulates dendritic cell activation by targeting STAT4 in the treatment of experimental autoimmune encephalomyelitis - Fang Zhou; Yu-Xin Guo; Rui Gao; Xiao-Yu Ji; Yu-Xuan Tang; Li-Bin Wang; Yuan Zhang; Xing Li (Toxicology and Applied Pharmacology, 2024)

Experimental study on the hydrodynamic performance of a side-by-side box-membrane breakwater - Jing-Ping Wu; Chuan-Rui Li; Jing-Jing Qi; Xing-Yu Xu; Jia-Ning Li; Xiu-Xing Zhang; Qing Qin; Zhi-Rong Zhou (Ocean Engineering, 2024)

Critical factors in soil organic carbon mineralization induced by drying, wetting and wet-dry cycles in a typical watershed of Loess Plateau - Yi Zhang; Xiaojun Liu; Peng Li; Lie Xiao; Shixuan Zhou; Xing Wang; Rui Wang (Journal of Environmental Management, 2024)

Composite porous 3D foam for solar-driven atmospheric water harvesting in low humidity natural environment - Jiyan Li; Guoyu Xing; Min Qiao; Silu Du; Tao Zhou; Shuo Gao; Hanxue Sun; Rui Jiao; An Li (Chemical Engineering Journal, 2024)

Two new sesterterpenoids from Atractylodes japonica Koidz. ex Kitam - Yuan-Yuan Zhou; Zhao Sun; Yan Liu; Zhen-Xing Fang; Hui-Rui Gao; Ning-Yu Liu; Xiao-Juan Zhang; Bing-You Yang; Hai-Xue Kuang (Journal of Natural Medicines, 2024)

Effect of nano-SiO2 modification on the seismic performance of recycled aggregate concrete shear walls - Yingwu Zhou; Liu Fan; Feng Xing; Wenwei Lin; Rui Hu; Menghuan Guo; Zhongfeng Zhu (Engineering Structures, 2024)

Refining granite generation by interrogation of zircon and monazite U-Th-Pb and Hf/Nd-O isotopes - Xing Zhang; Yuanbao Wu; Bin Fu; Wenxiang Zhang; Long Li; Guangyan Zhou; Rui Li; Zhaochu Hu; Yu He; Zhengwei Qin (Chemical Geology, 2024)

Seedless hydrothermal growth of piezoelectric photocatalytic ZnO nanowires on laser-ablated copper mesh for oil/water separation - Xiaohan Xing; Rui Zhou; Huangping Yan; Hongjun Liu (Journal of Environmental Chemical Engineering, 2024)

Numerical Simulation of the Mass Movement Process of the 2018 Sedongpu Glacial Debris Flow by Using the Fluid-Solid Coupling Method - Xing-Yu Long; Yu-Xiang Hu; Bin-Rui Gan; Jia-Wen Zhou (Journal of Earth Science, 2024)

Microplastics affect mosquito from aquatic to terrestrial lifestyles and are transferred to mammals through mosquito bites - Jian-hang Li; Xiao-hui Liu; Guo-rui Liang; He-ting Gao; Si-han Guo; Xin-yu Zhou; Dan Xing; Teng Zhao; Chun-xiao Li (Science of The Total Environment, 2024)

Spatial distribution characteristics of perfluoroalkyl substances in bulk and grain size fractionated sediments in Shenzhen Bay - Haoshuai Li; Zimin Wang; Yang Zhou; Cui Shi; Huayang Gan; Fang Chen; Lei Xing; Danxu Guo; Longhai Zhu; Nan Wang; Shuhong Fang; Rui Bao (Marine Pollution Bulletin, 2024)

Integrating bulk-RNA sequencing and single-cell sequencing analyses to characterize adenosine-enriched tumor microenvironment landscape and develop an adenosine-related prognostic signature predicting immunotherapy in lung adenocarcinoma - Tao Han; Jing Wu; Yafeng Liu; Jiawei Zhou; Rui Miao; Jianqiang Guo; Zhi Xu; Yingru Xing; Ying Bai; Dong Hu (Functional & Integrative Genomics, 2024)

Revealing the membrane fouling behavior and interfacial interaction mechanism in a combined visible light photocatalysis-ultrafiltration system for advanced purification of NOM - Rui Yu; Yanling Yang; Liping Tian; Xing Li; Chunjiao Liu; Tianjie Sun; Haiqing Chang; Zhiwei Zhou (Journal of Water Process Engineering, 2024)

Advances, challenges, and prospects in microalgal-bacterial symbiosis system treating heavy metal wastewater - Xing-Rui Zhou; Rong Wang; Cong-Cong Tang; Cristiano Varrone; Zhang-Wei He; Zhi-Hua Li; Xiaochang C. Wang (Chemosphere, 2023)

Strategy of functional nucleic acids-mediated isothermal amplification for detection of foodborne microbial contaminants: A review - Jie Zhou; Teng-Yu Wang; Zhi Lan; Han-Jie Yang; Xing-Jian Ye; Rui Min; Zhao-Hui Wang; Qing Huang; Jing Cao; Yu-E Gao; Wen-Long Wang; Xiu-Lan Sun; et al. (Food Research International, 2023)

Photocatalysis-Fenton mechanism of rGO-enhanced Fe-doped carbon nitride with boosted degradation performance towards rhodamine B - Fuwang Zhao; Yanling Yang; Siyang Ji; Rui Yu; Xing Li; Zhiwei Zhou (Journal of Water Process Engineering, 2023)

GRPR down-regulation inhibits spermatogenesis through Ca2+ mediated by PLCβ/IP3R signaling pathway in long-term formaldehyde-exposed rats - Yan-qi Yang; Rui-fang Sun; Pan Ge; Wen-Xing Li; Xiang Zhang; Jian Zhang; Lu Ye; Nan Zhang; Si-yu Wang; Mo-qi Lv; Dang-xia Zhou (Food and Chemical Toxicology, 2023)

Star-like, dopant-free, corannulene-cored hole transporting materials for efficient inverted perovskite solar cells - Ming-Wei An; Bolin Li; Bin-Wen Chen; Zuo-Chang Chen; Han-Rui Tian; Lin-Long Deng; Xugang Guo; Zhou Xing (Chemical Engineering Journal, 2023)

Pathogenicity characteristics of the entomopathogenic fungus Cordyceps javanica IJ-tg19 to Acyrthosiphon pisum - Di Wang; Pei-Xiang Xing; Hong-Liang Diao; Wen-Wen Zhou; Xian-Wei Li; Li-Jun Zhang; Rui-Yan Ma (BioControl, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Assessing the effects of short-term traffic restriction policies on traffic-related air pollutants - Xiao-Rui Fang; Xing-Hang Zhu; Xing-Zhou Li; Zhong-Ren Peng; Hu Qingyao; Hong-Di He; AJ Yuan Chen; Huang Cheng (Science of The Total Environment, 2023)

Highly sensitive surface-enhanced Raman scattering (SERS) imaging for phenotypic diagnosis and therapeutic evaluation of breast cancer - Chonggui Qiu; Wei Zhang; Yanhong Zhou; Hongwang Cui; Yanlong Xing; Fabiao Yu; Rui Wang (Chemical Engineering Journal, 2023)

Evolutions of upwelling and terrestrial organic matter input in the inner shelf of the East China Sea in the last millennium revealed by long-chain alkyl diols proxies - Chuanhui Song; Tianxiang Dang; Ting Zhang; Tiantian Ge; Rong Xiang; Lei Xing; Rui Bao; Yang Zhou; Rui Xiao; Baojin Wu (Frontiers in Marine Science, 2022)
Long-chain alkyl diols (LCDs) can be used as organic geochemical proxies for paleoceanographic change, especially in marginal sea areas where large volumes of sediments are deposited rapidly and continuously. However, little is known about the applicability and response on a millennium scale in relation with existing records in those sediments. We reconstruct changes in upwelling and terrestrial organic matter (OM) input in core sediments from the Zhejiang Fujian coastal station (T08) and Yangtze River Estuary station (T06) in the inner shelf of the East China Sea (ECS) over the last millennium, using the LCD based proxies: diol index 2 (DI-2), and FC 32 1,15-diol. Our results show that DI-2 values ([(C 28 +C 30 )1,14-diols]/([(C 28 +C 30 )1,13-diols]+[(C 28 +C 30 )1,14-diols])) at T08 decrease significantly during 600–400 yr BP but increase gradually after 400 yr BP. The FC 32 1,15-diol proxy ([C 32 1,15-diol]×100/([(C 28 +C 30 )1,13-diols]+[(C 30 +C 32 )1,15-diols])) at T06 shows marked fluctuations during 1000–800 yr BP, followed by a significant decline during 800–500 yr BP but a subsequent increase from 500 to 300 yr BP. We find that variations in DI-2 values are broadly consistent with changes in the strength of the East Asian Summer Monsoon (EASM) and the Kuroshio Current and are likely linked to changes in the frequency and intensity of the El Niño-Southern Oscillation (ENSO). The increased strength of the EASM causes greater offshore movement of the upper layer of seawater, which in turn triggers upwelling of bottom waters formed by Kuroshio subsurface waters. We find that variations in FC 32 1,15-diol proxy are controlled mainly by the East Asian Winter Monsoon (EAWM) and the Yangtze River discharge. By increasing the strength of the EAWM, southward transportation of material deposited in the estuary of the Yangtze River by the ECS coastal currents is promoted. In addition, we synthesize records of other organic geochemical indicators nearby core sediments in the ECS; these records emphasize the importance of reconstructing the evolutionary history of upwelling and subdividing the relative inputs of terrestrial OM. Our study provides a new means for reconstructing the evolution of upwelling and terrestrial OM input in the inner shelf of the ECS over the last millennium.

Modification of alternative splicing in bovine somatic cell nuclear transfer embryos using engineered CRISPR-Cas13d - Rui Cheng; Xiaoman Zheng; Yingmei Wang; Xing Ma; Xin Liu; Wenjun Xu; Mengyun Wang; Yuanpeng Gao; Xupeng Xing; Chuan Zhou; Hongzheng Sun; Zekun Guo; et al. (Science China Life Sciences, 2022)

Janibacter endophyticus sp. nov., an Endophytic Actinobacterium Isolated from the Root of Paris polyphylla Smith var. Yunnanensis - Zhen Zhang; En-Min Zhou; Cong-Jian Li; Xing-Wang Jiang; Rui-Feng Mao; Jing-Ran Liu; Xiao-Yang Zhi; Ling-Ling Yang (Current Microbiology, 2022)

Theoretical simulation of the selective stimulation of axons in different areas of a nerve bundle by multichannel near-infrared lasers - Rui Zhou; Zongxia Mou; Dandan Yang; Xing Wang (Medical & Biological Engineering & Computing, 2022)

Quantitative Proteomics Analysis of Sugarcane Ratoon Crop Chlorosis - Ye-Geng Fan; Rong-Fa Chen; Li-Hang Qiu; Zhong-Feng Zhou; Hui-Wen Zhou; Ji-Guang Wei; Xiu-Peng Song; Ting Luo; Prakash Lakshmanan; Xing Huang; Jian-Ming Wu; Yang-Rui Li (Sugar Tech, 2021)

Application of DNA barcoding and metabarcoding for species identification in salmon products - Nan Wang; Ran-Ran Xing; Meng-Yue Zhou; Rui-Xue Sun; Jian-Xun Han; Jiu-Kai Zhang; Wen-Jie Zheng; Ying Chen (Food Additives & Contaminants: Part A, 2021)

Paenibacillus puerhi sp. nov., isolated from the rhizosphere soil of Pu-erh tea plants (Camellia sinensis var. assamica) - Rui-Juan Yang; De Zhou; Qiao-Mei Wang; Xing-Hua Wang; Wen-Jie Zhang; Li Zhuang; Xuan-Jun Wang; Liang Yan; Jie Lv; Jun Sheng (Archives of Microbiology, 2021)

Effects of Exogenous GA3 and DPC Treatments on Levels of Endogenous Hormone and Expression of Key Gibberellin Biosynthesis Pathway Genes During Stem Elongation in Sugarcane - Li-Hang Qiu; Rong-Fa Chen; Han-Min Luo; Ye-Geng Fan; Xing Huang; Jun-Xian Liu; Fa-Qian Xiong; Hui-Wen Zhou; Chong-Kun Gan; Jian-Ming Wu; Yang-Rui Li (Sugar Tech, 2019)

Wind and sand control by an oasis protective system: a case from the southeastern edge of the Tengger Desert, China - Yun-hu Xie; Xiao-hong Dang; Zhong-ju Meng; Hong-tao Jiang; Xiao-jia Li; Rui-ping Zhou; Dan-dan Zhou; Xiao-xi Liu; Jing Ding; Xue-qin Wu; Yu-hao Wang; Chun-xing Hai; et al. (Journal of Mountain Science, 2019)

Effects of fine particle content and sample scale on the failure properties of loose landslide deposits - Bin-rui Gan; Xing-guo Yang; Ming-liang Chen; Jia-wen Zhou (Arabian Journal of Geosciences, 2018)

The influence of three mangrove species on the distribution of inorganic nitrogen and phosphorus in the Quanzhou Bay estuarine wetland soils - Guiyao Zhou; Yanyou Wu; Deke Xing; Mingming Zhang; Rui Yu; Weiyi Qiao; Qaiser Javed (Acta Geochimica, 2016)

Multiple Responsive Polymer-Peptide Bioconjugate - Xi-Rui Zhou; Rui Ge; Guofeng Li; Long Chen; Tianwei Tan; Xing Wang; Shi-Zhong Luo (International Journal of Peptide Research and Therapeutics, 2015)

Effect of Dietary Selenomethionine Supplementation on Growth Performance, Tissue Se Concentration, and Blood Glutathione Peroxidase Activity in Kid Boer Goats - Yu-xuan Song; Jin-xing Hou; Lei Zhang; Jian-gang Wang; Xiao-rui Liu; Zhan-qin Zhou; Bin-yun Cao (Biological Trace Element Research, 2015)

Meiothermus roseus sp. nov., a thermophilic bacterium isolated from a geothermal area - Hong Ming; Yan-Yan Duan; Qian-Qian Guo; Yi-Rui Yin; En-Min Zhou; Lan Liu; Shuai Li; Guo-Xing Nie; Wen-Jun Li (Antonie van Leeuwenhoek, 2015)

Baicalein inhibits prostate cancer cell growth and metastasis via the caveolin-1/AKT/mTOR pathway - Zhaoxin Guo; Xiaolin Hu; Zhaoquan Xing; Rui Xing; Renguang Lv; Xiangyu Cheng; Jing Su; Zunlin Zhou; Zhonghua Xu; Sten Nilsson; Zhaoxu Liu (Molecular and Cellular Biochemistry, 2015)

Heterologous expression and characterization of a novel halotolerant, thermostable, and alkali-stable GH6 endoglucanase from Thermobifida halotolerans - Yi-Rui Yin; Feng Zhang; Qing-Wen Hu; Wen-Dong Xian; Wael N. Hozzein; En-Min Zhou; Hong Ming; Guo-Xing Nie; Wen-Jun Li (Biotechnology Letters, 2015)

Streptomyces calidiresistens sp. nov., isolated from a hot spring sediment - Yan-Yan Duan; Hong Ming; Lei Dong; Yi-Rui Yin; Yi Zhang; En-Min Zhou; Lan Liu; Guo-Xing Nie; Wen-Jun Li (Antonie van Leeuwenhoek, 2014)

Roseomonas alkaliterrae sp. nov., isolated from an alkali geothermal soil sample in Tengchong, Yunnan, south-west China - Lei Dong; Hong Ming; Yi-Rui Yin; Yan-Yan Duan; En-Min Zhou; Guo-Xing Nie; Hui-Geng Feng; Lan Liu; Wen-Jun Li (Antonie van Leeuwenhoek, 2014)

Zhizhongheella caldifontis gen. nov., sp. nov., a novel member of the family Comamonadaceae - Lei Dong; Hong Ming; Lan Liu; En-Min Zhou; Yi-Rui Yin; Yan-Yan Duan; Guo-Xing Nie; Hui-Geng Feng; Wen-Jun Li (Antonie van Leeuwenhoek, 2014)

JNK Is Necessary for Oligodendrocyte Precursor Cell Proliferation Induced by the Conditioned Medium from B104 Neuroblastoma Cells - Jing-Xing Zhang; Yi-Fan Feng; Qi Qi; Lin Shen; Rui Wang; Jian-Sheng Zhou; He-Zuo Lü; Jian-Guo Hu (Journal of Molecular Neuroscience, 2014)

Vulcaniibacterium tengchongense gen. nov., sp. nov. isolated from a geothermally heated soil sample, and reclassification of Lysobacter thermophilus Wei et al. 2012 as Vulcaniibacterium thermophilum comb. nov. - Tian-Tian Yu; En-Min Zhou; Yi-Rui Yin; Ji-Cheng Yao; Hong Ming; Lei Dong; Shuai Li; Guo-Xing Nie; Wen-Jun Li (Antonie van Leeuwenhoek, 2013)

Re–Os molybdenite ages and zircon Hf isotopes of the Gangjiang porphyry Cu–Mo deposit in the Tibetan Orogen - Cheng-Biao Leng; Xing-Chun Zhang; Hong Zhong; Rui-Zhong Hu; Wei-De Zhou; Chao Li (Mineralium Deposita, 2013)

Molecular and cytological evidences for the natural wheatgrass hybrids occurrence and origin in west China - Jian Zeng; Xing Fan; Hai-Qin Zhang; Li-Na Sha; Hou-Yang Kang; Li Zhang; Rui-Wu Yang; Chun-Bang Ding; Yong-Hong Zhou (Genes & Genomics, 2012)

Phylogeny and molecular evolution of the DMC1 gene within the StH genome species in Triticeae (Poaceae) - Xiao-Li Wang; Xing Fan; Jian Zeng; Li-Na Sha; Hai-Qin Zhang; Hou-Yang Kang; Rui-Wu Yang; Li Zhang; Chun-Bang Ding; Yong-Hong Zhou (Genes & Genomics, 2012)

Proteomic Analysis of Osmotic Stress-Responsive Proteins in Sugarcane Leaves - Gui Zhou; Li-Tao Yang; Yang-Rui Li; Cheng-Lin Zou; Li-Ping Huang; Li-Hang Qiu; Xing Huang; Manoj Kumar Srivastava (Plant Molecular Biology Reporter, 2012)

Infectivity and propagation of attenuated infectious bursal disease virus in the chicken B-lymphocyte cell line DT40 - Jun Luo; Gai-Ping Zhang; Jian-Ming Fan; Man Teng; Lei-Ming You; Ling Zhou; Rui-Guang Deng; Xuan-Nian Wang; Yan-Yan Yang; Li Wang; Guang-Xu Xing; Na Cheng (Archives of Virology, 2009)

Phylogenetic Analysis of Leymus (Poaceae: Triticeae) Inferred from Nuclear rDNA ITS Sequences - Li-na Sha; Rui-wu Yang; Xing Fan; Xiao-li Wang; Yong-hong Zhou (Biochemical Genetics, 2008)

Cadmium accumulation in relation to organic acids in leaves of Solanum nigrum L. as a newly found cadmium hyperaccumulator - Rui-lian Sun; Qi-xing Zhou; Cai-xia Jin (Plant and Soil, 2006)